Assigning Economic Policy and Business Cycle Shocks to Democrats and Republicans: A Common Trends Approach - Göran Hjelm (Lund University, School of Economics and Management, Department of Economics, 2001)
We estimate a so called common trends model of federal taxes and spending in the U.S.. Using dates on presidential terms as well as the NBER business cycle, we are able to interpret the estimated permanent shock as being of structural policy origin and the transitory shock as being of (to politicians) exogenous business cycle origin. Apart from strong partisan effects, we find that Republicans attempts to reduce the public sector during the first half of the term and that Republicans also have been unlucky to have been in office during the major part of the negative (exogenous) business cycle shocks.
Keywords: C32; E61; H11; 330; Fiscal policy; Democrats; Republicans; Partisan differences; Common Trends